Endoscopic and histological characteristics of small bowel tumors diagnosed by double-balloon enteroscopy - Suleyman Dolu; Soner Onem; Zarni Htway; Farid Hajıyev; Ali Bilgen; Hatice Cilem Binicier; Ecem Kalemoglu; Ozgul Sagol; Mesut Akarsu (Korean Society of Gastrointestinal Endoscopy, 2023)
Background/Aims Double-balloon enteroscopy (DBE) allows for the diagnoses and treatment of small bowel tumors (SBTs). This study aimed to evaluate the utility of DBE for the diagnosis and treatment of SBTs. Methods Patients diagnosed with SBTs who underwent DBE were included in this study. According to their endoscopic appearances, they were categorized as polyps or masses, and according to their histological characteristics, they were categorized as benign or malignant SBTs. Results A total of 704 patients were retrospectively analyzed, and 90 (12.8%) were diagnosed with SBTs. According to their endoscopic appearance, 48 (53.3%) had polyps and 42 (46.7%) had masses. Additionally, 53 (58.9%) and 37 (41.1%) patients had malignant and benign SBTs, respectively, depending on their histological characteristics. Patients diagnosed with polyps were younger than those diagnosed with masses (p<0.001). Patients diagnosed with benign SBTs were younger than those diagnosed with malignant SBT (p<0.001). Overall, histological diagnosis was determined using DBE in 73 (81.1%) patients. Conclusions DBE is a useful method for diagnosing SBTs. Additionally, the histological type of the lesion can be determined using DBE.